Possible glendonite mineral pseudomorphs in the aftermath of the end-Permian extinction - Musaab Al-Sarmi; Rachel Wood (Scientific Reports)
Abstract Glendonites (from the precursor of ikaite, CaCO3.6H2O) preferentially precipitate within sediments in cold waters (− 2 to 7°C) via either organotrophic or methanogenic sulphate reduction. Here, we report the first occurrence of possible glendonites associated with the end Permian mass extinction in the earliest Triassic (ca. 252 Million years ago, Ma) subtropical marine carbonates on the Arabian Plateau, Oman. The authigenic carbonate crystals are small (< 2 mm) and precipitated either on bedding planes or reworked within micro cross-laminations, erosional scours, or lags at the base of calcisiltite turbidites, supporting a syn-depositional origin. The observed shape and macrostructure bear resemblance to that of glendonites. SEM and cathodoluminescent imaging reveals unzoned internal structures with three mineral phases: irregular, pseudo-hexagonal and spherical low-Mg calcite crystals (Type 1), low-Mg calcite cement (Type 2), and a later void-filling silica cement (Type 3). The pseudomorphs show δ13C values from − 0.14‰ to − 0.85‰ (mean − 0.43‰; n = 5) that are more positive than the associated micritic matrix, where values range from − 0.92‰ to − 2.39‰ (mean − 1.64‰; n = 7), indicating that oceanic dissolved inorganic carbon (DIC) was the primary carbon source rather than either methane or organic matter. These δ13C values significantly differ from typical δ13C signatures of authentic glendonites, except for Ordovician examples. If these are glendonites, we infer that they could have precipitated due to the unusually elevated alkalinity and pH (> 9) oceanic conditions present in the aftermath of the end-Permian extinction associated with highly disrupted carbon cycle dynamics, possibly accompanied with the upwelling of cold, anoxic oceanic water.